Tree fine roots productivity and turnover rates estimation in alpine sandy land - Feng, Lili; Jia, Zhiqing; Zhang, Zhaojiang (Bangladesh Journal of Botany, 2020)
Sequential coring method was used to collect the data of fine roots from June to August in alpine sandy land. Turnover rates were calculated by maximum or mean biomass during the growing season in 2015 using Decision Matrix (DM) or Maximum-Minimum (MM) method. Results show that biomass in June is lower than that in July and August. Turnover rates of Artemisia desertorum are higher than that of Caragana intermedia and Caragana korshinskii. Turnover rates of mixed forest are higher than that of pure forest. Soil gravimetric water content is highly related to root biomass/ length in the depth of 40 - 60 cm for Caragana intermedia and Caragana korshinskii. But soil gravimetric water content and root biomass/ length have no obvious regularity in the depth of 40 ~ 60 cm for Artemisia desertorum. The minimum water requirement threshold of around 0.02 can be acquired for Caragana intermedia and Caragana korshinskii in the arid region. In alpine sandy land, it is suitable to plant Artemisia desertorum compared to Caragana intermedia and Caragana korshinskii; mixed forest has more advantages compared to pure forest.